2013
DOI: 10.1111/1471-0528.12429
|View full text |Cite
|
Sign up to set email alerts
|

Hyperemesis gravidarum and birth outcomes—a population‐based cohort study of 2.2 million births in the Norwegian Birth Registry

Abstract: Objective To study associations between hyperemesis gravidarum (HG) and birth outcomes.Design Population-based cohort study.Setting Norway.Sample Singleton births in the Norwegian Birth Registry, 1967-2009 (n = 2 270 363).Methods Multiple logistic regression was applied to study associations between HG and dichotomous outcomes; multiple linear regression to study associations between HG, birthweight and gestational length. Generalised estimating equations were applied to obtain valid standard errors. Sub-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 26 publications
6
42
2
3
Order By: Relevance
“…The recent Norwegian Mother and Child Cohort Study reported that HG-exposed babies had slightly reduced birthweight, but there were no association between HG and SGA birth [18, 23], although it should be noted that no adjustment for weight gain was made, while adjusting for smoking status slightly increased the effect of HG. Further reports have suggested that HG does not influence birth weight [11, 16, 17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent Norwegian Mother and Child Cohort Study reported that HG-exposed babies had slightly reduced birthweight, but there were no association between HG and SGA birth [18, 23], although it should be noted that no adjustment for weight gain was made, while adjusting for smoking status slightly increased the effect of HG. Further reports have suggested that HG does not influence birth weight [11, 16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, severe maternal weight loss in early pregnancy, typically linked with extreme NVP, has been linked with growth restriction [9]. However, other reports have suggested that HG does not influence growth restriction [14, 15], birth weight [11, 16, 17], or risk for SGA [18]. Thus, there is as yet no clear consensus on this issue [11, 16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the influence of socio‐economic status on HG risk is inconsistent in the literature,33, 39, 40 but low socio‐economic status is associated with increased morbidity and mortality 41, 42, 43…”
Section: Methodsmentioning
confidence: 99%
“…Two large cohort studies in Scandinavian countries showed that hyperemesis was associated with higher risk of preeclampsia, lower birth weight and shorter gestational duration [15, 21]. This was supported by several studies suggesting higher risks of low birth weight (LBW), small for gestational age (SGA), and preterm birth if mothers experienced hyperemesis [2224].…”
Section: Introductionmentioning
confidence: 94%